Resistência anti-helmíntica em caprinos no município de Mossoró-RN - Coelho, Wesley Adson Costa (2009)
For many centuries the Brazilian Northeast area is vocation in the production of goats, in the which the gastrointestinal nematodes is among the largest problems. Even with the appearance of anthelmintic drugs of wide action spectrum, the control of the parasites has been harmed by the anthelmintic resistance. The purpose of this study was to verify the sensibility of the goat nematodes the action of the substance ivermectin 1% and albendazole 10% as well as to determine the profile of the properties that with resistant. The work was accomplished in 30 creations of goats located into Mossoró city between January to November 2008, where each property was divided in three groups, a control and two treatments. The obtained data were analyzed by statistical program RESO. In each property 45 animals were selected, divided in three groups: group I treatment benzimidazole, I group II ivermectin and I Group III, without treatment. The animals was drugged and 10 days powder-treatment was collection of feces, directly of the rectal flask and processing of the samples for the method of OPG and larva culture. The geographical coordinates of all the properties were obtained by GPS. The obtained data were analyzed by statistical program RESO. In studied the Haemonchus contortus, was the more prevalence in all the treated groups, and the population of resistant helmints to albendazole was 90% of the properties, while, the ivermectina 36.6%. Already Trichostrongylus sp, was found in 70% of the properties and your percentile of the population of resistant helmintos the ivermectina was of 33.3%, while the albendazole, 42.8%. The reduction in the count of eggs in the feces (RCEF) after 10 days of the treatment with ivermectina and albendazole, varied among 43% to 100%, 29% to 100% respectively. In resistance order the gender Haemonchus contortus was larger index, followed for Trichostrongylus sp and Oesophagostomun sp. The data of GPS revealed that 27 properties resistance to the albendazole were broadly distributed for every municipal district, concentrating at the areas west of the city of Mossoró-RN. The 13 resistant properties the ivermectin were distributed in the municipal district, but in smaller proportion that albendazole. In all resistant properties the ivermectin were simultaneously resistant albendazole. The profile of the properties demonstrated that the anthelmintic used was groups of the benzimidazole (63.3%), ivermectin (33.3%), in smaller scale the imidazol (3.3%). In these properties were not adopted correct handling of the animals as well as ignorance of the correct dose e drugs anthelmintic. The profile of the properties demonstrated that the anthelmintic used was groups of the benzimidazóis (63.3%), ivermectin (33.3%), in smaller scale the imidazol (3.3%). In these properties were not adopted correct handling of the animals as well as ignorance of the correct dose e drugs anthelmintic.